Social Media Narratives in Communities of Resistance - Knox, Stu (2015)
The Egyptian Revolution of 2011+ saw unprecedented involvement of Arab bloggers and online supporters participating in a process of political change. This paper will argue that a crucial factor in the success of the Egyptian protests was the recognition by protesters and their supporters, both national and transnational, of shared social identity constituted in resistance to injustice; the resulting community of resistance countered the exclusionary policies inherent and pervasive in the Egyptian government led by Hosni Mubarak from 1981 to 2011. Although the protests drew worldwide attention, and much scholarly research attempted to explain events and the role of social media in the Revolution and its outcomes, a neglected area of research remains in the analyses of Revolution social media narratives, which can be used to explore issues surrounding protester unification and the role of language in forging solidarity and developing communities of resistance. Analyses of the social media texts produced by Egyptian bloggers participating in the Revolution, and the subsequent online commentary those texts generated, provide opportunities to reflect upon and gain further understanding of the underlying issues framed within the online dialogic interactions generated by the texts, how those issues are addressed, and how online spaces are utilised.